A performance analytical model of automated material handling system for semiconductor wafer fabrication system. Issue 6 (18th March 2016) - Zhang, J.; Qin, W.; Wu, L.H.
Abstract : To effectively analyse and evaluate the performances of closed-loop automated material handling system (AMHS) with shortcut and blocking in semiconductor wafer fabrication system, a modified Markov chain model (MMCM) has been proposed. The system characteristics, such as vehicle blockage and system's shortcut configuration, are well considered in the MMCM. The state space explosion problem and computational challenge due to the increase of AMHS scale can be effectively eliminated. With production data from Interbay material handling system of a 300-mm semiconductor wafer fabrication line, the proposed MMCM is compared with simulation analysis model. The results demonstrate that the proposed MMCM is an effective modelling methodology for AMHS's performance analysis at system design stage.